On one class of integral functionals with a variable domain of integration - Shevchenko, A.I.; Minenko, A.S. (Reports of the National Academy of Sciences of Ukraine, 2014)
The potential-rotational current with free boundary is investigated. This variational task is equivalent to the problem of the minimum of an integral functional with a variable domain. The existence of the classical solution of a nonlinear boundary-value problem is proved.